ESTIMATION OF THE WAVE PARAMETERS DESIGNED IN THE SAOMAI - BENDINH, VUNGTAU SEAWATERS - Mau, Le Dinh (Vietnam Journal of Marine Science and Technology, 2009)
This paper presents the calculated results of wave parameters for design and construction of the nearshore hydro-structures such as wave height, wave period, wave length, longshore current speed induced by breaker in the Saomai-Bendinh, Vungtau seawaters corresponding to 50 years return period. Wind data were taken from Vungtau Station (1987 - 2006), extreme wind speed was calculated by FT-I distribution function; wave parameters in the offshore region were calculated by deep water wave model - Dolphin; wave parameters in the nearshore region were calculated by SWAN model. The studied results showed that Saomai - Bendinh seawaters was strongest affected by wave action from SW and W directions, especially in the area of shoals around Tau Islands and Longson. Dinh River channel was less affected by wave action. The typhoon No. 28 (11/1962) was strongest affected to study area which generated significant wave height of 1.0 to 2.0 m and 2.0 to 2.5 m in the area around and off Tau Islands respectively.